2021
DOI: 10.3389/fnut.2020.625178
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Diversity and Its Contribution in the Etiology of Maternal Anemia in Conflict Hit Mount Cameroon Area: A Cross-Sectional Study

Abstract: Background: In the Mount Cameroon area, maternal anemia remains a major public health concern. We hypothesized that nutrient inadequacy may account for the level of anemia in pregnancy. Thus, this study examined the relative effect of dietary diversity on maternal anemia in the study area.Methods: A total of 1,014 consenting pregnant women were enrolled in this cross-sectional study. Information on socio-demographic, antenatal characteristics, malaria and anemia control measures were documented. Dietary divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 59 publications
(58 reference statements)
5
21
0
Order By: Relevance
“…Only two components of PDQS were significantly associated with anaemia in pregnant women, in multivariate analysis: eating dark green leafy vegetables and consumption of vegetable oils were strongly associated with protection from anaemia. These findings are comparable with studies conducted in the Morogoro and Dodoma Regions of Tanzania, which found that women who consumed dark green leafy vegetables resulted had higher hemoglobin and overall iron status [37], as well as with research conducted in Cameroun which found that consumption of vegetables and dark green leafy vegetables were significantly associated with lower prevalence of anaemia in pregnant women [38]. It is evident that these findings call for national programs to enhance the knowledge and skills of pregnant women in terms of use of green leafy vegetables, methods of cooking, processing of greens and growing kitchen garden.…”
Section: Plos Global Public Healthsupporting
confidence: 82%
“…Only two components of PDQS were significantly associated with anaemia in pregnant women, in multivariate analysis: eating dark green leafy vegetables and consumption of vegetable oils were strongly associated with protection from anaemia. These findings are comparable with studies conducted in the Morogoro and Dodoma Regions of Tanzania, which found that women who consumed dark green leafy vegetables resulted had higher hemoglobin and overall iron status [37], as well as with research conducted in Cameroun which found that consumption of vegetables and dark green leafy vegetables were significantly associated with lower prevalence of anaemia in pregnant women [38]. It is evident that these findings call for national programs to enhance the knowledge and skills of pregnant women in terms of use of green leafy vegetables, methods of cooking, processing of greens and growing kitchen garden.…”
Section: Plos Global Public Healthsupporting
confidence: 82%
“…In the present study, women in second and third pregnancy trimester were more likely to be anaemic which aligns with earlier studies conducted in Bangladesh [17], Cameroon [31], Ethiopia [32]. The current study found that pregnant and lactating women who received antenatal care (ANC) four or more times during their pregnancy had a lower risk of being anemic, which is consistent with earlier studies [31,33]. This may be due to routine diagnosis of anaemia during the ANC visit, scheduled counselling on nutrition related knowledge, supplementation and treatment [31].…”
Section: Discussionsupporting
confidence: 92%
“…Inappropriate eating habits may contribute to the development of anaemia where low dietary diversity plays a signi cant role. In our study, anaemia among pregnant and lactating women was linked to the consumption of low-diversi ed diet which was consistent with earlier study [31,32]. The physiological state of high demanding nutrient during pregnancy and lactation period suggested women to consume a diversi ed diet to achieve nutrient adequacy to prevent the development of micronutrient de cient anaemia [32].…”
Section: Discussionsupporting
confidence: 91%
“…After a full‐text review, 42 studies were excluded for several reasons, including lack of full text, being outside the scope of the study, not presenting outcome measures, having different reference categories, and a high risk of bias. After a thorough review, 13 articles for the association between inadequate dietary diversity and anemia (Abriha et al, 2014; Agbozo et al, 2020; Ayensu et al, 2020; Delil et al, 2018; Deriba et al, 2020; Gibore et al, 2021; Jugha et al, 2021; Lebso et al, 2017; Ngimbudzi et al, 2021; Samuel et al, 2020; Vanié et al, 2021; Zerfu et al, 2016, 2019) and nine articles for determining the strength of the association between inadequate dietary diversity and low birth weight (Adem et al, 2020; Ahmed et al, 2018; Alemu & Gashu, 2020; Bekela et al, 2020; Berhe et al, 2021; Girma et al, 2019; Quansah & Boateng, 2020; Saaka et al, 2017; Zerfu et al, 2016) were included in the final meta‐analysis (Figure 1). One study was discarded after quality assessment (Vanié et al, 2021).…”
Section: Resultsmentioning
confidence: 99%